2017
DOI: 10.1159/000455942
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysregulation, Cognitive Impairment, and Symptoms of Psychosis as an Unusual Presentation in an Anti-Aquaporin 4-Positive Patient

Abstract: We present the unusual case of a patient with an aquaporin 4 antibody-seropositive neuromyelitis optica spectrum disorder who presented with autonomic dysregulation, cognitive impairment, and symptoms of psychosis. Only a few previous cases have been described with similar psychiatric symptoms. Brain MRI showed an abnormal hyperintense T2 signal of the hypothalamus and, to a lesser extent, a minor hyperintense signal of the right optic nerve. Her symptoms and MR abnormalities improved after high-dose methylpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The myriad of neuropsychiatric presentations of NMOSD can mimic all those encountered clinically in lupus, and we suggest after ruling infections in lupus, it's worthwhile testing for AQP4 positivity, as it portends a relapsing course, culminating in damage accrual, and a progressive neurological disability. Unusual presentations for NMOSD including psychosis, altered sensorium, cognitive disturbances, apraxia, catatonia, autonomic disturbances, syndrome of inappropriate diuretic secretion (SIADH), and symptomatic narcolepsy [25][26][27][28] can also overlap with neuropsychiatric manifestations of lupus. 4,29 Testing for AQP4 becomes imperative in any neuropsychiatric manifestations of lupus, especially the refractory or relapsing subset, to rule out concomitant NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…The myriad of neuropsychiatric presentations of NMOSD can mimic all those encountered clinically in lupus, and we suggest after ruling infections in lupus, it's worthwhile testing for AQP4 positivity, as it portends a relapsing course, culminating in damage accrual, and a progressive neurological disability. Unusual presentations for NMOSD including psychosis, altered sensorium, cognitive disturbances, apraxia, catatonia, autonomic disturbances, syndrome of inappropriate diuretic secretion (SIADH), and symptomatic narcolepsy [25][26][27][28] can also overlap with neuropsychiatric manifestations of lupus. 4,29 Testing for AQP4 becomes imperative in any neuropsychiatric manifestations of lupus, especially the refractory or relapsing subset, to rule out concomitant NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…The strong relations between biological stress, its anatomical substrates in the HPA axis, and psychosis, may contribute to the occurrences of secondary psychoses implicating these structures. In one case, incoherent and delusional thinking with self-neglect was observed in a patient who presented with hypothalamic lesions in the context of aquaporin 4 antibody seropositive neuromyelitis optica spectrum disorder (Ruiter et al 2017). In another, a hypothalamic hamartoma caused ictal psychosis, which manifested by episodes of sudden outbursts of aggressive and agitated behavior, with paranoid delusions.…”
Section: In Secondary Psychosismentioning
confidence: 97%
“…A number of patients experienced hypothalamic dysregulation (1). However, only a few cases reported patients with hypothalamic lesions and psychiatric symptoms (1,2). Our study found a patient with prominent hypothalamic dysfunction presented typical diencephalic lesions in the initial episode, which was not observed until 2 months after she was transferred to a specialized hospital.…”
mentioning
confidence: 99%